The influence of foliar application of calcium-containing preparations on apple orchard productivity and fruit quality - L. Shevchuk; V. Tonkha (Рослинництво та ґрунтознавство)
Effective production of high-quality and high-yielding fruit and berries is essential for addressing shortages. However, producers often encounter challenges related to calcium deficiency in apples. This study aimed to evaluate the productivity of late-ripening apple cultivars – Ligol, Jonagold Early Queen, and Fuji – following foliar application of calcium-containing preparations, as well as to assess the quality of their fruit. Field and laboratory research methods were employed to achieve this objective, and the results were subjected to statistical analysis. The study revealed that the Ligol cultivar exhibited the highest yield (19.3 t/ha) when treated with Brexil Ca at a rate of 1.8 L/ha. This represented an 8.3% increase compared to the control and a 12.9% increase compared to the variant treated with HelpRost at a rate of 1.0 L/ha. The highest fruit weight (296.5 g) was recorded for the Ligol cultivar when treated with Brexil Ca at a rate of 1.8 L/ha. Foliar application of Brexil Ca at the same rate was most effective for the Fuji cultivar, resulting in a yield of 24.8 t/ha, which was 9.8% higher than the control and 16.1% higher than the variant treated with Biocalcium (2.0 mL/ha) and HelpRost (1.0 L/ha). For the Jonagold Early Queen cultivar, the highest yield (16.2 t/ ha, 8.6% above the control) and fruit weight (249.8 g, 5.4% above the control) were achieved with HelpRost at 1.0 L/ha. The highest flesh firmness in the Ligol cultivar was observed with Biocalcium treatment (2.0 mL/ha), while in the Jonagold Early Queen and Fuji cultivars, it was achieved with HelpRost (1.0 L/ha). The findings provide practical insights for enhancing apple production efficiency, improving fruit quality, and extending storage life